Regulate yourself: Emotion regulation and protective behavioral strategies in substance use behaviors. (May 2019) - Blanchard, Brittany E.; Stevens, Angela; Cann, Adam T.; Littlefield, Andrew K.
Abstract: Although research suggests links between emotion regulation strategies and substance use outcomes, little work has examined the relationship between specific strategies (i.e., reappraisal and suppression) and outcomes (i.e., alcohol and cannabis consumption and related problems). To date, no research has examined the association between emotion regulation strategies and protective behavioral strategies used while engaging in substance use. Thus, the current study examined these relations for females and males. Undergraduates ( N  = 643) completed an online battery of self-report measures. Using structural equation modeling, results indicated improved Emotion Regulation Questionnaire model fit after one item was removed. Reappraisal was negatively associated with alcohol binge frequency and related problems for females, though suppression was negatively related to these outcomes for males. Reappraisal was also negatively associated with cannabis-related problems for males only. Reappraisal was positively associated with all types of protective behavioral strategies use for females, whereas only alcohol-specific serious harm reduction and cannabis protective behavioral strategies were significant for males. Latent variable interactions between reappraisal and protective behavioral strategies were significant for past-month cannabis use and related problems for males and indicated protective behavioral strategies use was more protective against past-month use and cannabis-related problems for those high in reappraisal. Although replication is necessary, these preliminary findings suggest the link between emotion regulation strategies and substance use outcomes among college students is complex and future work may benefit from examining these relations from an emotion regulation flexibility perspective. Highlights: Reappraisal was positively associated with alcohol- and cannabis-related PBS. Suppression was negatively associated with alcohol-related problems among males. Reappraisal and PBS use predicted fewer cannabis-related problems among males. Emotion regulation flexibility may be important for substance-related outcomes.